2015
DOI: 10.4238/2015.september.22.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of esterases in Euschistus heros (Hemiptera, Pentatomidae) and their relationship with thiamethoxam and lambda-cyhalothrin

Abstract: ABSTRACT. The brown stink bug Euschistus heros is the most abundant species of the soybean-sucking bugs, and causes large economic losses. Applying different chemical groups of organosynthetic insecticides for its control increases the potential for resistance. Esterases are a group of enzymes that play a variety of roles in insects, and some of them are related to the metabolism of xenobiotics. The aim of this study was to analyze the esterase isoenzyme system of this species and investigate its response to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Among these herbivorous pentatomids, the Neotropical brown stink bug, Euschistus heros (Fabricius) is most representative of this insect pest complex . E. heros damages soybeans by inserting its mouthparts into the pods while probing the seeds, causing seeds to become dry and wrinkled, resulting in abnormal maturity of the plants and a reduction in their oil content and germination rates, all of which affect the production and quality of the seeds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these herbivorous pentatomids, the Neotropical brown stink bug, Euschistus heros (Fabricius) is most representative of this insect pest complex . E. heros damages soybeans by inserting its mouthparts into the pods while probing the seeds, causing seeds to become dry and wrinkled, resulting in abnormal maturity of the plants and a reduction in their oil content and germination rates, all of which affect the production and quality of the seeds …”
Section: Introductionmentioning
confidence: 99%
“…For instance, despite the known benefits of using integrated and more sustainable practices, control of soybean insect pests still relies on insecticide applications at a rate of more five times per season . In Brazil, neonicotinoids and pyrethroids have become the most common insecticides used to control E. heros . The restricted number of chemicals registered for control of these insects and the indiscriminate use of this control practice will certainly lead to substantial biodiversity losses in agricultural landscapes, selection for insecticide‐resistant populations, resurgence and/or outbreaks of insect pests, and impairment of non‐target organisms, including humans …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study has disclosed that most genes associated with resistance are highly expressed in the epidermal layer of the seed tegument, which could prevent or lessen the action of the pesticide even before reaching the target site within the cells. Hegeto et al () showed distinct esterase enzyme patterns between strains of E. heros exposed or not exposed to the Engeo Pleno insecticide, indicating that alterations in the enzyme activity may be associated with the xenobiotic resistance mechanism. Collectively, the results of these studies suggest that metabolic changes may contribute to the development of resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to insecticides can be considered a concise model for natural selection. The intensive use of pesticides can develop the accumulation of several resistance mechanisms in surviving specimens (Zhu et al ), including metabolic changes associated with cytochrome P450 enzymes, glutathione S‐transferase and esterase (Liu et al ; Zhu et al ; Hegeto et al ). Zhu et al () conducted a study with susceptible and resistant populations of the bedbug Cimex lectularius Linnaeus, 1758, a hematophagous species of medical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Insect α ‐esterases play important physiological roles in xenobiotics detoxification and resistance development . The functions of α ‐esterases and β ‐esterases can bind to, sequester, and detoxify certain chemical pesticides, which can cause changes in the sensitivity of insects to these insecticides . Esterases are involved in the detoxification process of insecticides and convert them into low toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%